2018
DOI: 10.1063/1.5042847
|View full text |Cite
|
Sign up to set email alerts
|

Probing the non-equilibrium transient state in magnetite by a jitter-free two-color X-ray pump and X-ray probe experiment

Abstract: We present a general experimental concept for jitter-free pump and probe experiments at free electron lasers. By generating pump and probe pulse from one and the same X-ray pulse using an optical split-and-delay unit, we obtain a temporal resolution that is limited only by the X-ray pulse lengths. In a two-color X-ray pump and X-ray probe experiment with sub 70 fs temporal resolution, we selectively probe the response of orbital and charge degree of freedom in the prototypical functional oxide magnetite after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Results on time-resolved imaging (Gu ¨nther et al, 2011;Rath et al, 2014), spectro-temporal characterization of XUV pulses (Ding et al, 2021) and stimulated X-ray emission (Kroll et al, 2020) have also been reported. In recent years the technique of two-color pump/ probe experiments was utilized to reveal the non-equilibrium dynamics in diamond (Inoue et al, 2016) and magnetite (Pontius et al, 2018). The investigation of the temporal dynamic of systems is key to the fundamental understanding of its underlying physics.…”
Section: Introductionmentioning
confidence: 99%
“…Results on time-resolved imaging (Gu ¨nther et al, 2011;Rath et al, 2014), spectro-temporal characterization of XUV pulses (Ding et al, 2021) and stimulated X-ray emission (Kroll et al, 2020) have also been reported. In recent years the technique of two-color pump/ probe experiments was utilized to reveal the non-equilibrium dynamics in diamond (Inoue et al, 2016) and magnetite (Pontius et al, 2018). The investigation of the temporal dynamic of systems is key to the fundamental understanding of its underlying physics.…”
Section: Introductionmentioning
confidence: 99%
“…A prominent principle to explore the temporal dynamic of a system are pump-probe experiments which at FELs are mainly carried out in the ps-and sub ps-region. [1][2][3][4][5][6] . As pump-probe experiments include two pulses with a well-defined time delay between both, the temporal resolution of the experiment is given by the pulse duration of the two pulses and the achieved accuracy of the temporal delay between them.…”
Section: Introductionmentioning
confidence: 99%
“…There is special scientific interest in two-color FEL pulses with time delay and central photon energy separation both adjustable. Among the use cases are pump-probe [7][8][9], coherent stimulated X-ray Raman spectroscopy [10][11][12], and multi-wavelength anomalous diffraction [13] experiments.…”
mentioning
confidence: 99%